A human tail arising from the anal mucocutaneous junction: A case report. (September 2021) - Ibrahim, Hussein; Maher, Ahmed; Fouad, Hesham Fayek; Sabra, Tarek Abdelazeem
Abstract: Introduction: Human tails are rare congenital malformations that describe protrusions commonly located around the midline of the lumbosacral region covered by skin, representing an embryonic remnant. Human tails are broadly classified into true and pseudo-tails. The real ones represent the persistence of a remnant of the embryonic tail formed between the fourth and eighth week of gestation. Presentation: A male infant aged 42 days presented to our institution with a tail-like structure that originated from the anal mucocutaneos junction. The parents did not bring the baby at birth because of the social stigma and ignorance. On examination, there was a tail-like structure that is about 22 cm in length and 1.5 cm in diameter originated from the mucocutaneous junction at the anus at the left side. There was no bony element on palpation. The lower vertebral column examination showed no abnormalities, and this was confirmed with an x-ray. The patient was operated on with simple excision of the tail and primary closure of the wound at the base. He was discharged on the same day well and good. The tail was taken for microscopic histopathology. Discussion: There are few reported cases describing human tails. However, none of them was originating from the anal mucocutaneous junction. Conclusion: We report the first case of a human tail arising from the anal mucocutaneous junction worldwide. Due to its very superficial origin, it was not associated with any other anomalies. Highlights: Human tails are rare congenital protrusions located commonly around the midline of the lumbosacral region It is the first reported case worldwide of a human tail arising from the anal mucocutaneous junction. We performed a simple excision of the tail and a primary closure of the defect and the tail was sent for histopathological examination